Baritan Tradition Cultural Transformation, Strengthening of Religiosity, and Patriotism in the Community of Blitar District - Inayati, Isna Nurul (Proceedings of Annual Conference for Muslim Scholars, 2024)
Every year in the month of Muharram, the residents of Blitar District practice an old tradition known as baritan as a show of gratitude and a request for protection from any misfortunes. This tradition has changed over time in several ways, including ritual practices, the venues where these events are held, and the intentions why they are performed. This study was conducted out to explore this further. The study applies a Phenomenology study methodology alongside with a qualitative approach. The Siraman Village in the Kesamben District of the Blitar District serves as the research locus. Purposive sampling was implemented to select respondents, and documentation, interviews, and observation were used to collect data. The results of this research showed that the Baritan tradition has changed in terms of both its cultural content and its intended usage. These changes are meant to make sure that the Baritan tradition remains as a cultural practice that everyone in the community, accept, perform, and preserve. Especially the younger generation, whom often begins ignoring ancestral traditions. The cultural changes are intended to increase the community's commitment to appreciate diversity and enhance its beliefs of religiosity and patriotism.